2019
DOI: 10.2174/1874447801913010035
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Investments in New Transport Technologies such as HSR on the Tourism Industry

Abstract: Background: The transportation industry and the tourism market are related to each other. Specifically a place with an efficient transportation system can be in general considered a good tourist destination. Objective: In this manuscript, the objective is to demonstrate whether the presence of High Speed Rail can affect tourists' choices of a given destination for their holidays. The case study of Italy has been taken into account. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…However, this factor is more effective for HICs and UMICs. The findings from Pagliara et al (2019) also conformed to our results, which showed that high-speed transport significantly affects tourist arrival and length of stay. This result reflects the inadequacy of transport infrastructure in LMICs and LICs.…”
Section: Resultssupporting
confidence: 90%
“…However, this factor is more effective for HICs and UMICs. The findings from Pagliara et al (2019) also conformed to our results, which showed that high-speed transport significantly affects tourist arrival and length of stay. This result reflects the inadequacy of transport infrastructure in LMICs and LICs.…”
Section: Resultssupporting
confidence: 90%
“…An increasing number of studies have focused on the effect of the HSR system on tourism. They cover research scope, such as countries (T. Huang et al, 2019), provinces (He et al, 2021), and economic belts (Yang & Li, 2020), and focus on temporal and spatial evolution (Pagliara & Mauriello, 2019), the relationship (Jou & Chen, 2020), development efficiency (Zeng et al, 2021), the time-space compression effect (T. , influencing factors (Holesˇinska´et al, 2022), and the expost effects (Albalate et al, 2022). With the development of HSR construction, some scholars have also conducted joint research on the HSR system and sustainable tourism, especially in the pattern.…”
Section: Sustainable Tourism Supported By Hsrmentioning
confidence: 99%
“…They cover research scope, such as countries (T. Huang et al, 2019), provinces (He et al, 2021), and economic belts (Yang & Li, 2020), and focus on temporal and spatial evolution (Pagliara & Mauriello, 2019), the relationship (Jou & Chen, 2020), development efficiency (Zeng et al, 2021), the time-space compression effect (T. Li et al, 2022), influencing factors (Holešinská et al, 2022), and the ex-post effects (Albalate et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%